1984
DOI: 10.1159/000241779
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Effects of Isoproterenol Infusions in Young Swine

Abstract: The cardiovascular and renal effects of intravenous (i.v.) and intra-arterial (i.a.) infusions of isoproterenol (ISP, 0.1–0.2 μg/kg/min) were evaluated in 17 two-week-old swine anesthetized with pentobarbital. The glomerular filtration rate (GFR) of each kidney and blood flow and vascular resistance (RVR) of the left kidney were determined in all animals. In the 8 animals given ISP i.v., right ventricular pressure and dP/dtmax were also determined via a thoracotomy. In 9 animals, ISP was given i.a. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…facilitates the matu---, rational increase in renal blood flow, remain largely unexplained. Previous investigations to explain the developmental phenomenon of renal hernodynamics have focused o n vasoconstrictor mechanisms such as an increased sympathoadrenergic response (8)(9)(10)(11)(12)(13), the highly activated renin angiotensin system (14)(15)(16), or activation of the prostanoid thromboxane ( 17). Prostaglandins, the only vasodilators examined, may participate in fetal renal hemodynamics (18) but have not been proven to regulate basal renal hemodynamics in the developing animal (1 5).…”
mentioning
confidence: 99%
“…facilitates the matu---, rational increase in renal blood flow, remain largely unexplained. Previous investigations to explain the developmental phenomenon of renal hernodynamics have focused o n vasoconstrictor mechanisms such as an increased sympathoadrenergic response (8)(9)(10)(11)(12)(13), the highly activated renin angiotensin system (14)(15)(16), or activation of the prostanoid thromboxane ( 17). Prostaglandins, the only vasodilators examined, may participate in fetal renal hemodynamics (18) but have not been proven to regulate basal renal hemodynamics in the developing animal (1 5).…”
mentioning
confidence: 99%
“…Little is known about the ontogeny of sympathoadrenal stimulated renal vasodilation. Buckley et al (6,7) have examined the postnatal development of renal vasodilatory mechanisms in anesthetized piglets (6, 7). Their studies have shown that the Padrenergic vasodilatory mechanism in the renal vascular bed of swine is absent at birth and appears postnatally at 2 wk.…”
mentioning
confidence: 99%
“…The ontogeny of adrenergic receptors is still ill-defined in newborn mammals. In piglets studied at birth and subsequently at different postnatal ages [3,4], a vasoconstrictor tonus mediated by a-adrenergic innervation was present since birth. However, the response to nerve electric stimulation intensified with postnatal age and animals of less than 4 days only responded to high frequency stimulation.…”
Section: Discussionmentioning
confidence: 99%